Instant sedimentation in a deep Alpine lake (Iseo, Italy) controlled by climate, human and geodynamic forcing. Issue 4 (14th February 2022) - Rapuc, William; Arnaud, Fabien; Sabatier, Pierre; Anselmetti, Flavio S.; Piccin, Andrea; Peruzza, Laura; Bastien, Antoine; Augustin, Laurent; Régnier, Edouard; Gaillardet, Jérôme; Von Grafenstein, Ulrich
Abstract: The sedimentary processes in the deep basin of large peri‐Alpine lakes have not been studied much on long timescales due to high coring complexity of such lake systems. In 2018, a 15.5 m long sediment section was retrieved from the deep basin of Lake Iseo (Italy) at 251 m water depth. A seismic survey associated with a multi‐proxy approach using sedimentological and geochemical analyses, reveals that event deposits correspond to 61.4% of the total sedimentation during the last 2000 years. The great heterogeneity of textures, colours and grain‐size distribution between the different types of event layers can be explained by the high number of potential sources of sediment in this large lake system. By combining a proxy of sediment sources with proxies of transport processes, flood events were distinguished from destabilizations of the slopes and the main delta. The three thickest mass wasting deposits correspond to major regional earthquakes events of 1222 ce, 1117 ce and around 700 ce . From a thorough comparison with regional climatic fluctuations and human activities in the watershed, it appears that periods of high sediment remobilization can be linked to a preceding increase in erosion in the watershed mainly under human forcing. Hence, even in large catchments, human activities play a key role on erosion processes and on sediment availability, disrupting the recording of extreme events in lacustrine archive.